Data Mining: A Tutorial Base Primer - Richard J Roiger (Pearson Education, 2005)
This primer on data mining provides an introduction to the principles and techniques for extracting information from a business-minded perspective. A basic familiarity with the field of data mining concepts is built and then enhanced via 13 data mining tutorials. Upon completion of these tutorials students will be fully able to data mine. This book is appropriate for students of CS MIS and Information Technology.